A SOCIOPRAGMATIC ANALYSIS OF APOLOGIZING EXPRESSIONS IN ENGLISH DRAMA MOVIES - PRATIWI, EMMY MARTHA (2010)
This research is aimed at classifying the implied meanings (implicatures) and the politeness strategy in the apologizing expressions of apologizing expressions in English drama movies. The type of this research is descriptive qualitative research. The method of collecting data is documentation. The writer classified the data by referring the context of situation based on Nunan and Grice's cooperative principle (maxims). And then she analyzing the politeness strategies of apologizing expressions by classifying the data into four types of politeness strategies described by Brown and Levinson (1978: 96). This study shows the variety implicature of apologizing expressions in English drama movies. There are 2 categories of the meaning of apologizing expression that are: Conversational Implicature and Conventional Implicature. The implied meanings of apologizing expressions are blaming, complaining, joking, mocking, flattering, expressing embarrassment, promising and confusing. There are some pattern politeness strategies of apologizing expressions that are: Bald On-Record, Positive Politeness, Negative Politeness and Off-Record Indirect Strategy.